Genetic and evolutionary analysis of emerging HoBi-like pestivirus. (July 2021) - Guo, Zhiyuan; Wang, Lin; Niu, Lingdi; Shangguan, Haikun; Huang, Chengshi; Yi, Ying; Zhang, Yannan; Gao, Mingchun; Ge, Junwei
Abstract: HoBi-like pestivirus, an emerging species within the Pestivirus genus, is an important pathogen associated with a variety of clinical manifestations of ruminants, especially cattle. HoBi-like pestiviruses were identified in several countries and from different hosts, and raised concerns with regard to their acute and persistent infections, which is implicated in economic losses for cattle farmers. However, the transmission path, codon usage bias, and host adaptation of the virus has not been studied. Hence, we performed the analysis the spatio-temporal transmission based on the available 5'-UTR sequences of HoBi-like pestivirus, and then conducted codon analysis of the complete coding sequence of the virus. The results show the virus appeared in 1952 (95% HPD: 1905–1985) and may have originated in India. In addition, Italy is the hub for the spread of the virus. Moreover, six potential recombination events and two complex recombination events were discovered. Analysis of codon usage patterns revealed that the effective number of codon (ENC) values with an average of 50.85, and the codon usage bias is greatly affected by natural selection, which is different from the previous BVDV-1, 2. Finally, codon adaptation index (CAI) analysis shows that pigs may be the potential origin species of the HoBi-like pestivirus. These findings will contribute to more effective control of the spread of the virus, extend the knowledge about the genetic and evolutionary features of HoBi-like viruses and provide some information for vaccine research. Highlights: The spatio-temporal transmission of HoBi-like pestivirus was analyzed for the first time. India is estimated the geographical origin of HoBi-like pestivirus. Unlike the previous BVDV, the codon usage bias of HoBi-like pestivirus is greatly affected by natural selection.